2010
DOI: 10.1111/j.1365-2311.2009.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in defensive behaviour between host‐adapted races of the pea aphid

Abstract: Abstract. 1. Host races, i.e. host-adapted populations in partial reproductive isolation, have been reported in a growing number of insect herbivores including aphids. The pea aphid Acyrthosiphon pisum encompasses distinct races highly specialised on various Fabaceae plants. Races have been well documented at both the ecological and genetic level. However, little is known about possible behavioural differences between host races other than those involved in plant choice.2. The aim of this study was to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…Not all clones produced all phenotypes and clones differed in their dropping tendency (mean behavior). Similarly, Kunert, Belz, Simon, Weisser, and Outreman (2010) showed that clones that originated from different host plants species (i.e., host races, populations that are adapted to their host species) varied in their mean escape response when reared on the same host plant species. Our results suggest, that the escape behavior is not genetically fixed per se (in that case we would expect all individuals of one clone to show the same behavior) but that response rules are genetically determined (Houston & McNamara, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Not all clones produced all phenotypes and clones differed in their dropping tendency (mean behavior). Similarly, Kunert, Belz, Simon, Weisser, and Outreman (2010) showed that clones that originated from different host plants species (i.e., host races, populations that are adapted to their host species) varied in their mean escape response when reared on the same host plant species. Our results suggest, that the escape behavior is not genetically fixed per se (in that case we would expect all individuals of one clone to show the same behavior) but that response rules are genetically determined (Houston & McNamara, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…This is because the high diversification of this group of animals may partly result from adaptive processes that reflect their specialization to different host plants (i.e., higher affinity to feed and reproduce on a particular plant) and associated assortative behavior among individuals within a group on one host plant-type potentially leads to reduced gene flow between groups feeding on different host plants [3]–[5]. In such cases, insect species form “host races” that are often a first step toward eventual sympatric speciation [3], [6]. These host races form, potentially leading to divergent selection via reproductive isolation [3], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although wingless aphids mostly are sedentary and can only walk a relatively short distance, their dispersal behaviors are also important for aphids population (Braendle et al, 2006; Brisson, 2010; Irwin et al, 2007), and this has been confirmed by several studies (Phelan et al, 1976; Alyokhin and Sewell, 2003; Kunert et al, 2010; Ben-Ari et al, 2015). Comparing with fully developed winged aphids, wingless aphids have degenerations in some of their sense organs and lose locomotion abilities, resulting in different dispersal ranges (Braendle et al, 2006; Bromley et al, 1980; Kring, 1977; Moran, 1992; Park and Hardie, 2002).…”
Section: Discussionmentioning
confidence: 65%
“…Studies on apterae of Macrosiphum euphorbiae and Myzus persicae showed different dispersal behaviors and moment abilities (Alyokhin and Sewell, 2003). Many apterous aphids could increase their rate of locomotion and decrease their orientation to vertical image after being dislodged by an alarm pheromone (Phelan et al, 1976; Kunert et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation